Effect of weather and time on trauma events determined using emergency medical service registry data. Issue 9 (September 2015) - Lin, Li-Wei; Lin, Hsiao-Yu; Hsu, Chien-Yeh; Rau, Hsiao-Hsien; Chen, Ping-Ling
Abstract Introduction Trauma admissions are associated with weather and temporal factors; however, previous study results regarding these factors are contradictory. We hypothesised that weather and temporal factors have different effects on specific trauma events in an emergency medical service (EMS) system. Methods EMS data from January 1, 2009, to December 31, 2010, were obtained from the fire department of Taipei City and associated with the local weather data. EMS trauma events were categorised into total trauma, traffic accidents (TAs), motorbike accidents (MBAs), and falls. Hourly data on trauma patients were analysed using the zero-inflated Poisson model. Results The hourly incidence of total trauma increased with the magnitude of precipitation (incidence rate ratio [IRR] = 1.06, 1.09, and 1.11 in light, moderate, and heavy rain, respectively), and this effect was more prominent in fall patients than in patients with other injuries (IRR = 1.07, 1.21, and 1.32). However, the hourly incidence of TAs and MBAs was associated only with light rain (IRR = 1.11 and 1.06, respectively). An hour of sunshine exposure was associated with an increase in the hourly incidence of all groups, and higher temperatures were associated with an increased hourly incidence of total trauma, TAs, and MBAs, but not falls. The hourly incidence of falls increased only in late fall and winter. Compared with the hourly incidence between 3 am and 7 am, the hourly incidence of all groups plateaued between 7 am and 11 pm and declined from 11 pm to 3 am. During the plateau period, 2 peaks in the incidence of TAs (IRR = 5.03 and 5.07, respectively) and MBAs (IRR = 5.81 and 5.51, respectively) were observed during 7–11 am and 3–7 pm. The hourly incidence of total trauma, TAs, and MBAs plateaued during workdays, peaked on Fridays, declined on Saturdays, and troughed on Sundays. The incidence of falls increased only on Mondays (IRR = 1.09). Conclusions Weather and temporal factors had different impacts on the incidence of traffic-related accidents and falls. Therefore, EMS data may have implications in preventing injuries and planning resource use for prehospital trauma rescue.